The Dominance of Law Enforcement Authority in the Investigation Stage: A Critical Analysis of Law Enforcement Effectiveness and Abuse of Power - Bari Candramedi (International Journal of Law, Crime and Justice, 2026)
The investigation stage constitutes a crucial phase in the criminal justice system, as it determines the direction and quality of subsequent law enforcement processes. Within the context of Indonesian criminal procedural law, the Criminal Procedure Code (Kitab Undang-Undang Hukum Acara Pidana/KUHAP) grants extensive authority to law enforcement officials, particularly investigators, in order to ensure the effective disclosure of criminal offenses. However, such dominance of authority has the potential to create an imbalance between the interest of law enforcement effectiveness and the protection of human rights, especially when it is not accompanied by adequate mechanisms of limitation and oversight. This study aims to critically analyze the dominance of law enforcement authority at the investigation stage and its implications for law enforcement effectiveness and the potential for abuse of power. The research employs normative legal research using statutory and conceptual approaches, supported by qualitative analysis of legal doctrines, legislation, and relevant academic literature. The findings indicate that while the dominance of investigative authority does contribute to the effectiveness of investigations, it simultaneously creates opportunities for abuse of power due to weak internal and external oversight mechanisms. This condition results in the erosion of the principles of due process of law and the protection of suspects’ rights within the criminal justice system. Therefore, this study emphasizes the need to strengthen judicial control mechanisms, enhance the accountability of law enforcement officials, and reform criminal procedural law in order to achieve a balance between effective law enforcement and the protection of human rights within a democratic rule-of-law state.